2010
DOI: 10.1001/archsurg.2010.272
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Access to Care and Survival for Patients With Early-Stage Hepatocellular Carcinoma

Abstract: For early-stage HCC, racial/ethnic disparities in survival between minority and white patients are notable. After accounting for differences in stage, use of invasive therapy, and treatment benefit, no racial/ethnic survival disparity is evident between Hispanics and whites, but blacks have persistently poor survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
105
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 12 publications
10
105
3
Order By: Relevance
“…Multiple studies have shown that black patients are less likely to receive surgical management of HCC, which is generally an option for patients with better preserved liver function [11,[14][15][16]. Sloane and his colleagues reported that black patients with localized HCC defined as disease confined to the initial organ without evidence of spread were more likely to have "surgery not recommended" (45% versus about 37%) and less likely to have "surgery performed" (20% versus 30%) when compared to white patients (p<0.001) [11].…”
Section: Differences In Presentation Treatment and Survival Among Afmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple studies have shown that black patients are less likely to receive surgical management of HCC, which is generally an option for patients with better preserved liver function [11,[14][15][16]. Sloane and his colleagues reported that black patients with localized HCC defined as disease confined to the initial organ without evidence of spread were more likely to have "surgery not recommended" (45% versus about 37%) and less likely to have "surgery performed" (20% versus 30%) when compared to white patients (p<0.001) [11].…”
Section: Differences In Presentation Treatment and Survival Among Afmentioning
confidence: 99%
“…Mathur, et al found that black and Hispanic patients received invasive therapy defined as tumor ablation, hepatectomy or liver transplant at lower rates than whites and Asians (p<0.001) [14]. The authors cited poor access to complex cancer care as a potential contributor to this disparity.…”
Section: Differences In Presentation Treatment and Survival Among Afmentioning
confidence: 99%
See 3 more Smart Citations